Does agricultural worker density moderate the relationship between physician supply and low birth weight? Evidence from U.S. counties - Brousseau, Melanie A., author; Pena, Anita Alves, advisor; Basow, Benjamin, advisor (Colorado State University. Libraries, 2026)
Migrant and seasonal farmworkers face disproportionate health risks due to occupational exposure, geographic isolation, and structural barriers to care, but the supply-side capacity of healthcare systems serving agricultural communities is understudied at the population level. This study addresses that gap by investigating whether primary care physician supply predicts low birth weight rates at the county level and whether agricultural worker density moderates that relationship across United States counties. Using a cross-sectional design, this study utilizes county-level data sourced from the 2025 County Health Rankings, the 2022 USDA Census of Agriculture, the Healthy Resources and Services Administration Federally Qualified Health Center site database, the 2021 American Community Survey, and Kaiser Family Foundation Medicaid expansion records. These datasets are linked through Federal Information Processing Standard codes and encompass approximately 2,700 counties. The primary analysis estimates a moderated linear regression model in which the percentage of low-birth-weight births serves as the outcome, primary care physicians per 100,000 population serves as the independent variable, and agricultural worker density serves as the moderating variable. Results indicate a statistically significant negative interaction between physician supply and agricultural worker density (B3 = -0.118, p < 0.01), indicating that as agricultural worker concentration increases, the association between physician supply and low birth weight rates becomes steeper. These findings suggest that county-level physician supply measures alone may not fully capture effective healthcare access in agricultural communities.
Keywords: farmers; rural; healthcare; migrant and seasonal farmworkers